2013
DOI: 10.7868/s0026898413020079
|View full text |Cite
|
Sign up to set email alerts
|

Изменение Экспрессии Генов, Вовлеченных В Биосинтез Ретиноевой Кислоты, При Раке Желудка

Abstract: All-trans-retinoic acid (ATRA) is the main biologically active metabolite of retinol (vitamin A) that is required for the regulation of such processes as embryogenesis, tissue differentiation, proliferation, and others. Multiple alcohol, retinol and retinaldehyde dehydrogenases (ADHs, RDHs and RALDHs) as well as aldo-keto reductases (AKRs) catalyze the biosynthesis of retinoic acid in humans. For many normal and neoplastic tissues, the key ATRA-synthesizing enzymes remain unknown. We identified ATRA-generating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…RDH12, an NADPH-dependent retinal reductase, catalyzes the reduction of all-trans retinal to all-trans retinol (Belyaeva et al, 2005). It was significantly decreased in gastric tumor samples (Kropotova et al, 2013) and cervical squamous cell carcinoma samples (Peng et al, 2015). RDH12 was also one of the differentially expressed metabolism-related genes, and correlated with the prognosis of gastric cancer patients (Wen et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…RDH12, an NADPH-dependent retinal reductase, catalyzes the reduction of all-trans retinal to all-trans retinol (Belyaeva et al, 2005). It was significantly decreased in gastric tumor samples (Kropotova et al, 2013) and cervical squamous cell carcinoma samples (Peng et al, 2015). RDH12 was also one of the differentially expressed metabolism-related genes, and correlated with the prognosis of gastric cancer patients (Wen et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…AKR1B1 , aldo-keto reductase family 1, member B1, catalyzes the reduction of aldehydes including the aldehyde form of glucose. It was reported to be downregulated in endometrial cancer and gastric cancer [37,38]. The product of CHST10 , carbohydrate sulfotransferase 10, is known to inhibit the invasiveness of melanoma cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical analysis has revealed that AKR1B10 is localized in the rapidly renewing epithelial cells of the colon [ 68 ] and stomach [ 69 ]. In contrast, AKR1B10 is markedly decreased or undetectable in cancerous lesions of the colon [ 68 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ] and stomach [ 69 , 77 , 78 , 79 ] ( Table 3 ), as well as in precancerous lesions of the colon (including ulcerative colitis), Crown’s disease, and adenomatous polyps [ 68 , 73 ]. Zu et al [ 73 ] reported that AKR1B10 is critical for protecting host cells from DNA damage induced by electrophilic carbonyl compounds, which are ingested and/or metabolically formed in the intestine.…”
Section: Akr1b10 In the Gastrointestinal Tract And Cancermentioning
confidence: 99%